A Benign but Unusual Radiological Sign During EVAS Follow-up. (April 2017) - Bonardelli, Stefano; Ravanelli, Marco; Paro, Barbara; Battaglia, Giuseppe
Purpose: To report a heretofore undescribed complication seen on imaging after endovascular aortic sealing (EVAS).Case Report: A 77-year-old woman was treated with the Nellix EVAS device for an infrarenal aortic aneurysm. After a normal computed tomography (CT) scan at 15 days, the 6-month CT showed the onset of perianeurysmal inflammatory tissue. The patient was asymptomatic, and blood tests were normal. Imaging suggested a nonaggressive inflammatory process, so a conservative approach was adopted with close follow-up. The periaortic tissue remitted without any treatment after a further 9 months (16 months after EVAS).Conclusion: The cause of this nonacute complication is unclear. Some clues suggest that interaction between the endobags and aneurysm wall could be involved. Imaging and clinical data led to a successful conservative strategy.